Contemporary Challenges Facing Social Enterprises and Community Organisations Seeking to Understand Their Social Value. (2nd January 2017) - Kay, Alan; McMullan, Lisa
ABSTRACT: Both authors of this article have been involved with the Social Audit Network since it was incorporated in 2003. They have actively practised social accounting and audit (SAA) with a wide range of organisations across the UK and internationally. Much of the authors' work has been in helping organisations apply social accounting and audit. This article will consider the wider issues of understanding social value involving reflections on the experience gained over the years and will then tackle some of the of the emerging challenges . In conclusion, the authors look to the future and the common understanding of the social and community value generated by social enterprises and community organisations .